Comparative Study of Antimicrobial Efficacy of Azithromycin and Cefixime against Salmonella Typhi Infection - Thapa, Raj Kumar; Shrestha, Sagar (Journal of Manmohan Memorial Institute of Health Sciences, 2020)
Correction: The page numbers were changed from 84-97 to 67-80 on 31/08/2020. Introduction: Enteric fever is systemic infection caused by the Salmonella enteric serovars typhi and para typhi A B and C. It is the significant cause of morbidity and mortality. It occurs in all parts of the world where water supplied and sanitation is substandard. Annually, it is estimated that more than 10 million cases and 100000 deaths are caused by typhoid fever. Regarding to the strains, a high prevalence of S. typhi and S. paratyphi. A strains in Nepal that showed resistance against the quinolone nalidixic acid (MIC> 256 mcg/ml with a corresponding decreased susceptibility against fluoroquinolones such as ciprofloxacin (MIC>0.125 mcg/ml. Objectives: The main objective of study was to compare the efficacy of Azithromycin and Cefixime in treatment of typhoid fever. Methodology: The in vitro antibacterial activity of azithromycin and Cefixime against 4 isolated colonies of Salmonella typhi from reference of salmonella typhi ATCC no. 14028 and blood culture isolates from three different hospitals was evaluated by disc diffusion (well) method. 0.25 ppm, 0.5 ppm, 4 ppm, 8 ppm, 32 ppm, 128 ppm concentration of both Azithromycin and Cefixime was used. The zone of inhibition was measured and data was analyzed using Excel. Results: In all isolates of Salmonella typhi, the zone of inhibition shown by both Azithromycin and Cefixime is same at low concentration (0.25ppm, 0.5ppm) but with increasing in concentration there is increase in difference in zone of inhibition shown by them. The zone of inhibition shown by Cefixime is greater in high concentration as compared to zone of inhibition shown by Azithromyci. Conclusion: Our result indicate Cefixime is better than Azithromycin in therapeutic option for enteric fever.